Designing & conducting ethnographic research an introduction - LeCompte, Margaret Diane; Schensul, Jean J.; IG Publishing (Lanham, Md. AltaMira Press, 2010)
The Ethnographer's Toolkit series begins with this primer, which introduces novice and expert practitioners alike to the process of ethnographic research, including answers to questions like: who should and can do ethnography, when it is used most fruitfully, and how research projects are carried out from conceptualization to the uses of research results. Written in practical, straightforward language, this new edition defines the qualitative research enterprise, links research strategies to theoretical paradigms, and outlines the ways in which an ethnographic study can be designed. Use Designing and Conducting Ethnographic Research as a guide to the entire Toolkit or as a stand-alone introduction to ethnographic research.
What is ethnography? -- When, where, and by whom should ethnography be used? -- Paradigms for framing the conduct of ethnographic research -- An overview of research design -- Choosing and designing an ethnographic research question -- Collecting ethnographic data -- Data analysis : how ethnographers make sense of their data -- Identifying and building research teams and research partnerships -- Applying ethnography -- Protection of risk to human subjects and the ethics of ethnographic fieldwork.
Electronic reproduction.
Keywords: Ethnology -- Research; Ethnology -- Methodology; Research -- Evaluation; Electronic books